Emulsification properties of polysaccharides from Dioscorea opposita Thunb. (15th April 2017) - Ma, Fanyi; Zhang, Yun; Wen, Yurong; Yao, Yanna; Zhu, Jinhua; Liu, Xiuhua; Bell, Alan; Tikkanen-Kaukanen, Carina
Highlights: Molecular weights of Dioscorea opposita polysaccharides were in different ranges. The synergistic effect on emulsification properties of polysaccharides with gum arabic. Sample 2 and 3 showed emulsifying properties with medium-chain-triglycerides. Sample 2, gum arabic and triglycerides (1:1:1) presented the best emulsification. Abstract: This study investigated the emulsification properties of polysaccharides from Dioscorea opposita Thunb. Graded alcohol precipitation was used to extract Dioscorea opposita polysaccharides fractions (4 samples) in different ranges of molecular weight. Sample 3 contained more glucose and protein (80.13% and 0.34%, respectively), and molecular weight was approximately 34, 790 Da, distributing narrowly. The droplet sizes and stabilities of emulsions made of gum arabic (GA) and polysaccharide samples at different concentrations and ratios were measured, specifically the emulsions of GA and medium-chain-triglycerides (MCT); polysaccharides and MCT; and polysaccharides, GA and MCT (1:1:1). The results indicated that sample 2 and 3 had emulsifying properties, and the emulsions made with sample 2, GA and MCT (1:1:1) presented the best emulsification properties. Therefore, polysaccharides of Dioscorea opposita could be utilised as a natural emulsifier that can be improved synergistically with other emulsifiers, such as gum arabic.